Development of the Selection Process in our Republic and its Practical Significance - Jamshid Yuldashev Qambaraliyevich; Umarov Akbarjon Axrorjon o‘g‘li (Zien Journals, 2022)
This article contains information about the scientific work carried out in recent years in the field of selection of the cotton growing industry of our republic. The achievements of the conducted scientific researches are analyzed
Keywords: Cotton; fiber; fiber thickness; grade